2012
DOI: 10.1155/2012/845143
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Male Breast Cancer in Zaria, Nigeria

Abstract: Male breast cancer is an uncommon disease accounting for only 1% of all breast cancers. We present the evaluation, treatment and outcome of male patients seen with breast cancer in our institution. Male patients that had histological diagnosis of breast cancer from 2001 to 2010 were retrospectively evaluated. After evaluation patients were treated with modified radical mastectomy. Combination chemotherapy was given to patients with positive axillary lymph nodes. Radiotherapy and hormonal therapy were also empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 26 publications
(66 reference statements)
6
46
2
Order By: Relevance
“…5.6% patients presented with early gastric cancer. 12 In the present study the prevalence of gastric carcinoma was 4.46%, with male: female ratio of 3:1 and mean age of 50years.The prevalence of carcinoma stomach was more common in rural areas and poor socio economic status. Sixty percent of patients who consumed mixed diet suffered from carcinoma stomach.…”
Section: Resultssupporting
confidence: 45%
“…5.6% patients presented with early gastric cancer. 12 In the present study the prevalence of gastric carcinoma was 4.46%, with male: female ratio of 3:1 and mean age of 50years.The prevalence of carcinoma stomach was more common in rural areas and poor socio economic status. Sixty percent of patients who consumed mixed diet suffered from carcinoma stomach.…”
Section: Resultssupporting
confidence: 45%
“…Peritoneal metastasis is usually associated with a poor prognosis in patients with GC[3]. It may be ineffectual for patients with peritoneal metastasis to merely undergo gastrectomy and regional lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the lack of symptomatology and specific diagnosis, the 5-year survival rate of the disease is unfortunately extremely low because patients generally have high-stage disease when diagnosed[2]. Among factors leading to a poor prognosis, peritoneal metastasis is an indispensable indicator[3,4]. A previous study[4] demonstrated that peritoneal metastasis, which accounted for 50% of deaths, is the most important contributing factor of mortality in patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…Databases show that up to 93% of MBC cases are of advanced disease, and that distant metastases are observed in approximately 30% of these patients at the time of diagnosis (19,46). In the current study, the most frequent involvements were bone (n=12, 70.6%), lung (n=6, 35.3%), cranial field (n=3, 17.6%), brain (n=2, 11.8%), liver (n=2, 11.8%), pleura (n=1, 5.9%), and mesentery (n=1, 5.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the most frequent involvements were bone (n=12, 70.6%), lung (n=6, 35.3%), cranial field (n=3, 17.6%), brain (n=2, 11.8%), liver (n=2, 11.8%), pleura (n=1, 5.9%), and mesentery (n=1, 5.9%). There are other case series that reported different metastatic sites, among which were bones (48.78%), lungs (29.26%), liver (17.07%), spine (up to 30%), skin, and pleura (19,46).…”
Section: Discussionmentioning
confidence: 99%